Analisis Determinan Tingkat Pengungkapan Laporan Keuangan Pemerintah Provinsi di Indonesia - Uci Febriani; Junita Putri Jana Harahap (Regress: Journal of Economics & Management, 2021)
The aims this research is to examine and analyze the determinants of the level that affect the government. The sample in this study is the financial statements of local governments in Indonesia in 2017-2019. The sampling method used in this research is purposive sampling method, and the analysis model used is multiple regression analysis. The results of this show that regional wealth has an effect on the size of the provincial government's financial statements, while the number of OPD, local governments and the number of audit findings have no effect on the level of government financial statements. The average level of financial reporting in Indonesia in the 2017-2019 period was 58.35%, with the lowest level being North Kalimantan Province in the 2017 period at 43% and the highest government level being East Java Province in the 2017 period at 69%.